Mudanças de uso da terra em paisagens agrícolas com palma de óleo (elaeis guineensis jacq.). E implicações para a biodiversidade arbórea na Amazônia oriental Belém - (:unkn) unknown (Museu Paraense Emilio Goeldi, 2015)
The expansion of oil palm in the Amazon is associated with a number of public policy, in the form of actions and programs and has provoked economic and ecological changes in the region and challenge the society to monitor and control the palm cultivation expansion on a large scale. The municipalities from the "Palm region" in Pará state, as Moju, intensified cultivation of this palm tree and suffered intense modifications in thier natural ecosystems. In Addition this new frontier of bioenergy challenged the paradigm of sustainability, with social and environmental conflicts and replacement of subsistence farming by the palm. Little is known about the consequences that a large-scale monoculture can cause in the amazonian environment. To follow this new productive dynamic with palm oil are required interdisciplinary studies that contribute to identify how environmental respond to changes associated to the new agricultural frontier with oil palm. In this context, the overall objective of this research is to analyze the changes, the conflicts and the trajectories of land uses, as well as the value of conservation of the biodiversity of the plantations of oil palm and other land uses predominate in eastern Pará. The work is organized into five chapters including the first one which introduce the subject of the thesis. The other four are guided by the following specificobjectives: a) analyze the land use conflicts in Moju county, Pará state, Brazil, within areas of permanent preservation -PPA, according with the Brazilian Forest Code of 2012; b) map and quantify the types of land cover and land use in 2013 in three areas (Ubá, Arauaí e Mamorana), where the implementation of oil palm cultivation is present; c) capture the space-time variability in the changes of trajectories in landscapes of 1991-2013 and identify the effect of changes of land use in the structure of the landscape; and d) investigate the variation in the carbon stock and species richness of trees in different land use and vegetation cover in the three studied areas. For the study of conflicts in APPs in Moju, were used 29 multispectral images of high resolutions by RapidEye satellite of 2010. The results show that the area destined legally for permanent preservation (APP) in Moju is 47,357.06 ha, representing 5.21% of the municipal area. The PPAs with natural vegetation represent 68.60% of the APPs of the municipal area, about 28% of the PPAs have use conflicting with predominance of pasture in 15.6%. Only 0.63% of APPs is occpupied by palm oil. The application of the new recomposition guidelines for APPs according to the new Forest Code will result in the loss of 60.69% of the APP-recovered areas in this municipality. The analysis of vegetation cover and land use in 2013 in the three selected areas (Ubá, Arauaí and Mamorana) was made by the method of decision tree in images of the satellite Landsat-8 year of 2013. The overall performance of the classification was 0.87% (index kappa). The results show greater extension of primary forests in Mamorana, area in the beginning of cultivating oil palm. Agriculture predominate in all areas analysed. For the analyses of trajectories changes of land uses and the effects on the landscape structure i the landscape we made classification using decision tree method in images of the satellite Landsat TM-5 for the years 1991, 1995, 2001, 2005 and 2010, and Landsat-8 for the year 2013, through the ImgToos programs, ENVI and ArcGIS. The landscape structure was carried out through the landscape metrics (PLAND, LPI, PD and PROX-MN) using the FRAGSTATS program. v. 3.3. The classification achieved overall performance of 0.87% for the kappa index. In the period 1991-2013 the conversion of primary forest to other uses occurred in a ratio of 47.82%, while the degraded forest (17%) and oil palm (11%) had the largest increase in occupancy in 2013. We emphasize that the transition of the primary forest to palm oil was 20% in the 22 years under study, which led to a PD (fragments density index) with considerable amounts, attaining a level from 0.3 to 4.5 (number of patches/ 100 ha). Such conversions define the fragmentation intensity of primary forest. The investigation about the biodiversity response and carbon stocks in different forest cover and land uses was made through a floristic inventory of trees greater than or equal to 2 cm DBH in plots ranging from 1, 500 and 2500 m2 on each forest cover/land use analyzed. Intheall 8.55 ha sampling were registered 5,770 individual trees, distributed in 425 species and 74 families. The primary forest presented carbon stock higher than 80 Mg/ha, while palm oil, pasture and secondary forest presented less than 50 Mg/ha, noting that the oil palm retains impoverished communities of trees, and its tree composition is poorer than the pasture, while the stock of carbon is higher. In this study, in 22 years of the analysis we observed that primary forests covers less than 30% of the landscape, a critical level for biodiversity conservation.
Changes in land use in agricultural landscapes with oil palm (elaeis guineensis jacq.). And implications for tree biodiversity in the eastern Amazon Belém
Keywords: Palma de óleo; Biodiversidader; Estoque de carbono; Uso da terra; Cobertura vegetal; Sensoriamento remoto; CNPQ::CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS